2015
DOI: 10.1080/07315724.2015.1080548
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Dietary Interventions and Supplements to Improve Performance during Athletic Training

Abstract: Despite the numerous positive effects of physical exercise, some negative physiological changes occur in long-lasting heavy training with transient dysfunction of the immune system, increased inflammation, and oxidative stress. This is the case of elite athletes, who train intensively to compete at the highest levels. However, these athletes can counteract the negative effects of heavy training, reducing acute and chronic inflammations and supporting the immune system, with nutritional and supplementation coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
1
14
0
4
Order By: Relevance
“…Exercise performance may also be improved by enhancing postexercise recovery, which may enable greater tolerance to training. One approach to improving training tolerance is to increase the availability of antioxidants which neutralise exercise-induced free radicals and thereby have the potential to reduce muscle damage 8 9. Additionally, NO may promote postexercise muscle repair through activation of satellite cells involved in muscle remodelling and hypertrophy,10 and through increased blood flow, which may enhance nutrient replenishment and muscle protein synthesis in fatigued muscle 11…”
Section: Introductionmentioning
confidence: 99%
“…Exercise performance may also be improved by enhancing postexercise recovery, which may enable greater tolerance to training. One approach to improving training tolerance is to increase the availability of antioxidants which neutralise exercise-induced free radicals and thereby have the potential to reduce muscle damage 8 9. Additionally, NO may promote postexercise muscle repair through activation of satellite cells involved in muscle remodelling and hypertrophy,10 and through increased blood flow, which may enhance nutrient replenishment and muscle protein synthesis in fatigued muscle 11…”
Section: Introductionmentioning
confidence: 99%
“…The decreased after-intervention lymphocyte levels along with observed moderate effect size for increasing neutrophils and the concomitant rise in Neutrophils-to-Lymphocytes ratio for the PRO condition together with the absence of changes in cellular immune markers in the CHO group would reinforce the aforementioned statement that carbohydrates would be an effective nutrient to effectively counteract exercise-induced cellular immune dysfunction in endurance athletes [3,29]. Nonetheless, as previously discussed, both groups consumed a similar amount of total daily carbohydrates during the intervention.…”
Section: Discussionmentioning
confidence: 90%
“…Although from prospective long-term studies there has been demonstrated an inverse association between physical activity and inflammatory markers, particularly interleukin 6 (IL-6) (9), increased IL-6 and IL-8 levels were also reported following a 3-day period of intense physical running training (2.5 h/day) (26). Similarly, the transient dysfunction of the immune system, increased inflammation with a chronic increase in IL6, and oxidative stress are negative effects of physical exercise, which occurred in long-duration heavy training athletes (27). Thus, our results also help to clarify some benefits regarding the effects of EPA + DHA on adiponectin and IL6 homeostasis in overweight women with moderate physical activity.…”
Section: Discussionmentioning
confidence: 99%